Android phone : remote control for Nikon and Canon DSLR cameras - Mohamed Ashraf Abu Samah. (2012)
The Android mobile devices has now advanced far enough that it allows for many new technological capabilities. One of the capabilities being explored is the USB Host capability that allows it to control a slave device. With this capability, it is possible for an Android mobile device to control a DSLR camera remotely using only a USB cable.